2021
DOI: 10.1111/bju.15554
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of prostate cancer prediction models in men undergoing both magnetic resonance imaging and transperineal biopsy: Are the models still relevant?

Abstract: To externally validate and compare the performance of the European Randomized Study of Screening for Prostate Cancer risk calculator 3/4 (ERSPC-RC3/4), the Prostate Biopsy Collaborative Group risk calculator (PBCG-RC) and the van Leeuwen model to determine which prediction model would perform the best in a contemporary Australian cohort undergoing transperineal (TP) biopsy. Materials and MethodsA retrospective review identified all patients undergoing TP biopsy across two centres. Of the 797 patients identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…This manuscript is the first external validation study testing RC-R and RC-A in two centers within a "real-life" scenario. Contrary to previously published validation studies [11][12][13][14][15][16][17][18], our validation cohort had significant heterogeneity. We included patients with mpMRIs not performed by dedicated uro-radiologists but multiple radiologists with differing degrees of expertise.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This manuscript is the first external validation study testing RC-R and RC-A in two centers within a "real-life" scenario. Contrary to previously published validation studies [11][12][13][14][15][16][17][18], our validation cohort had significant heterogeneity. We included patients with mpMRIs not performed by dedicated uro-radiologists but multiple radiologists with differing degrees of expertise.…”
Section: Discussionmentioning
confidence: 69%
“…Most recently, various research groups implemented mpMRI findings into the ERSPC-RC. Among these, the RCs of Radtke et al [9] and Alberts et al [10] showed the most promising results in internal and external validation studies [11][12][13][14][15][16][17][18]. As mpMRI quality is highly dependent on the radiologist's experience, among other factors, it is unclear whether these RCs accurately predict the risk of PCa and csPCa when including mpMRI reports not performed by dedicated uro-radiologists.…”
Section: Introductionmentioning
confidence: 99%
“…We compared six methods that have been proposed for handling missing data with the objective of finding the method most likely to perform well in multiple external validation studies of a globally accessible online risk tool. As with all online risk tools, online publication of the original PBCG continues to result in published external validation studies providing evidence for or against its generalizability to other populations, particularly in comparison to other published tools [4,[21][22][23][24][25][26]. To date, by exclusion of prostate volume, the original PBCG tool has competed less favorably with the other tools incorporating this information.…”
Section: Discussionmentioning
confidence: 99%
“…We compared six methods that have been proposed for handling missing data with the objective of nding the method most likely to perform well in multiple external validation studies of a globally accessible online risk tool. As with all online risk tools, online publication of the original PBCG continues to result in published external validation studies providing evidence for or against its generalizability to other populations, particularly in comparison to other published tools [21,22,23,24,25,26,27]. To date, by exclusion of prostate volume, the original PBCG tool has competed less favorably with the other tools incorporating this information.…”
Section: Discussionmentioning
confidence: 99%